Long run Association of Stock Prices and Crude Oil Prices: Evidence from Saudi Arabia - Rahman, Abdul (International Journal of Energy Economics and Policy, 2020)
An efficient stock market is a sign of a resilient economy. It is also an indicator of investors' confidence in the macroeconomic fundamentals of the economy. The association of oil prices and health of the stock market for a predominantly oil-based economy also serves as an indicator of the attempted diversification going on in the economy since the inception of the National Transformational Program 2020. The current research attempts to investigate the relation of oil price changes with stock market prices of Tadawul for the period from 2000 to 2017 by using the Vector Auto Regression (VAR) methodology framework. The results show a long-run association between crude oil price and stock prices of Tadawul, and no short-run association is found between them. Keywords: stock prices, crude oil prices, long run association, stock market JEL Classifications: C13, G10, G12 DOI: https://doi.org/10.32479/ijeep.8881